In silico Evidence for Binding of Pentacyclic Triterpenoids to Keap1-Nrf2 Protein-Protein Binding Site - M. Kamble, Sarika; M. Patel, Harun; N. Goyal, Sameer; N. Noolvi, Malleshappa; B. Mahajan, Umesh; Ojha, Shreesh; R. Patil, Chandragouda (Combinatorial Chemistry & High Throughput Screening, 2017)
Aim and Objective: Kelch like ECH-associated protein 1 (Keap1) and Nuclear factor-E2 related factor 2 (Nrf2) binding is a key step in the ubiquitination and degradation of Nrf2. The compounds inhibiting this binding exert antioxidant actions. Naturally occurring pentacyclic triterpenoids (PTs) and their synthetic derivatives are projected as activators of Nrf2 signalling. The 16-mer Nrf2 peptide binding site on Keap-1 (PDB: 2 FLU) is proposed to be the prospective target where pentacyclic triterpenoid may exert protein-protein interaction. Material and Method: In the present study, seventy seven PTs of natural and synthetic origin are screened for Nrf2 stimulatory activity using online PASS (Prediction of Activity Spectrum of Substances) software followed by in silico molecular docking against 16-mer Nrf2 peptide binding site on Keap-1. This virtual screening reveals that Nrf2 stimulatory PTs dock on the 16-mer peptide binding site on Keap-1 and may exert their biological activities by interfering with the Keap-1 and Nrf2 binding. Results: In the present study shows that the small molecules like PT’s bind to keap 1 pocket where the 16 mer peptide of Neh2 domain of Nrf2. High docking score of -10.53, -9.08, -8.36, -7.94, -7.49 and -7.18 is shown by glycyrrhizin, asiatic acid, medecassic acid, barrigenic acid, rotundic acid, ursolic acid, respectively. Conclusion: The identified hits such as asiatic acid and medecassic acid represent a very promising starting point for the development of potent Nrf2 stimulator. The natural PTs are more promising than the most potent synthetic derivatives of oleanolic acid like CDDO, CDDO-methyl and CDDOimidazol.
Keywords: 16-mer binding sites